2018
DOI: 10.1155/2018/6074808
|View full text |Cite
|
Sign up to set email alerts
|

Current Strategies of Endocrine Therapy in Elderly Patients with Breast Cancer

Abstract: Currently, the growing population of the elderly is one of biggest problems in terms of increase in geriatric diseases. Lack of data from large prospective studies on geriatric breast cancer patients often makes it difficult for clinicians to make treatments decisions for them. Because both benefit and risk of treatment should be taken into account, treatment is usually determined considering life expectancy or comorbidities in elderly patients. Treatment of breast cancer is differentiated according to histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…ER and PR positivity is more common in elderly patients than in younger patients [ 6 , 33 ], indicating that the elderly are more likely to be sensitive to endocrine therapy. Additionally, endocrine therapy offers great benefit to elderly patients considering its equivalent efficacy to chemotherapy with a low risk of toxicities if appropriately used [ 34 ]. Although the conventional treatment for breast cancer is surgical resection, several prospective clinical trials have indicated much better outcomes for older patients with small, HR-positive tumors who receive tamoxifen alone than surgery [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…ER and PR positivity is more common in elderly patients than in younger patients [ 6 , 33 ], indicating that the elderly are more likely to be sensitive to endocrine therapy. Additionally, endocrine therapy offers great benefit to elderly patients considering its equivalent efficacy to chemotherapy with a low risk of toxicities if appropriately used [ 34 ]. Although the conventional treatment for breast cancer is surgical resection, several prospective clinical trials have indicated much better outcomes for older patients with small, HR-positive tumors who receive tamoxifen alone than surgery [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hospital visits are necessary to evaluate the effectiveness of endocrine therapy and for timely recognition of disease progression. All these aspects are associated with non-adherence (Holland et al, 2013;Lee & Seo, 2018) and might burden patient and their caregivers (Jayani & Hurria, 2012). Furthermore, knowing that there is a risk of tumour grow without surgical treatment, might lead to distress in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, mammography screening is confidently recommended for women over 50 years old, although women aged 40–50 years are also at risk of BC ( McDonald et al, 2016 ; Nelson et al, 2016 ; Phi et al, 2018 ). Various molecular subtypes of BC that require different therapy ( EBCTCG, 2015 ; Guerrero-Zotano & Arteaga, 2017 ; Lee & Seo, 2018 ), individual patient susceptibility to drugs and side effects from drugs ( Potosky et al, 2015 ; Greenlee et al, 2017 ; Moo et al, 2018 ) and the development of drug resistance ( Li et al, 2020 ; Zhong et al, 2020 ) make treatment of this disease more difficult and complicated. The listed difficulties indicate the need for study of new biomarkers that can help in the early detection, diagnosis and prognosis of BC.…”
Section: Introductionmentioning
confidence: 99%